Clinical Characteristics and Outcomes of Paediatric Patients with Coronavirus Disease (COVID-19): A Single Center Study in Bangladesh (Bangladesh Journal of Child Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has spread around the world and reports of children with COVID-19 are increasing. This study was conducted to assess clinical features and outcome of COVID-19 in children at Evercare hospital Dhaka.Materials & Method: This observational study was conducted on RT-PCR positive COVID-19 admitted children up to 14 years of age from May 2020 to November 2020 at the Pediatric Department of Evercare hospital Dhaka. Data were analyzed after collection of demographic and clinical data of 14 enrolled children.Results: The mean age of the study population was 2.8±3.8 years with male female ratio was 1:1. Two (14.3%) patients had H/O fever in family member & the mean duration between contact & appearance of symptom was 12.5±12.56 days. The major clinical symptom was fever (85.7%). Next most common presenting symptoms were loose stool, vomiting & abdominal pain (42.9%), and convulsion (28.6%). Cough and breathing difficulty were present in 21.4% & 14.3% of the patients respectively. Most of the cases diagnosed as AGE (42.8%) followed by febrile convulsion (28.5%) then pneumonia (21.4%).Conclusion: The symptoms of COVID-19 in children are mild and most of the patients may present with gastrointestinal symptoms such as loose stool, abdominal pain and febrile convulsion. The findings from this study might help to make early appropriate diagnosis and thus control the epidemic.BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 15-18